Book Review – Promoting Economic Cooperation in South Asia: Beyond Safta - Mohd, Saidatulakmal (Penerbit Universiti Sains Malaysia (USM Press), 2011)
Although known as the poorest region and faced with many internal conflicts, South Asia has much potential to be one of the leading regions in the world. As addressed by the many topics in this paper, South Asia has many economic advantages such as trade, tourism, transportation and employment. Hence, economic cooperation among the countries in the region has to be established and strengthened. The theme of this book is current, relevant and shows the importance of establishing economic cooperation in South Asia not only to benefit the South Asian countries but the world too. The arrangement of the book with thematic segment dealing with very specific topics provided easy understanding on the importance and directions of economic cooperation in South Asia. The strength of this book is the extensive information each author provided on the topics. The main weakness is the failure of the many authors to provide critical views and rigorous analysis on the addressed topics especially on why the countries failed to achieve economic integration in the region with regards to the specific issues addressed.